An Artefactual Cluster of Mycobacterium abscessus Pneumonia among Cancer Patients Arising from Contamination - Giusy Diella; Giuseppina Caggiano; Francesco Triggiano; Marco Lopuzzo; Francesca Apollonio; Michele Mastria; Luigi Ronga; Lucia Bonadonna; Luca Lucentini; Antonia Pece; Pietro Milella; Maria Teresa Montagna (Pathogens, 2022)
The Mycobacteriumabscessus complex (MABC) is a group of rapidly growing, nontuberculous mycobacteria that are ubiquitous in soil, urban water pipes, swimming pools, and drinking water. Members of the MABC are considered opportunistic pathogens. The aim of this study was to investigate the origins of MABC detected in broncho-lavage (BL) samples from asymptomatic cancer patients. We turned our attention to washing and disinfection procedures for bronchoscopes; we also assessed water and disinfectant samples. Of 10 BL and 34 environmental samples tested, four BL samples (40%) and seven environmental samples (20.6%) tested positive for MABC. We hypothesized that contamination could arise from the prewashing machine and/or the water used because no patient had clinical or radiological signs consistent with MABC respiratory tract infection. Our study highlights the importance of evaluating cleaning and disinfection procedures for endoscope channels to reduce the potential spread of microorganisms and artefactual results arising from contamination.